English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

f(t) tsint

2006-11-28 07:53:02 · 3 answers · asked by julia t 1 in Science & Mathematics Mathematics

3 answers

well first you have to get the first derivative

so: the 1st derivative= t*cost+1*sint
= cost^2+sint
then you take the derivative of that
so: the 2nd derivative= 2cost*-sint+cost
= -2sintcost+cost

2006-11-28 08:00:16 · answer #1 · answered by lifewithgooli 1 · 0 0

The second derivative is the derivative of the derivative.

2006-11-28 16:00:08 · answer #2 · answered by j 4 · 0 0

You must use the product rule:

f´(t) = 1*sin(t) + t*cost = sin(t) + t*cos(t)

And again:

f´´(t) = cos(t) + 1*cos(t) + t*(-sin(t)) = 2cos(t) - t*sin(t)

2006-11-28 16:33:15 · answer #3 · answered by vahucel 6 · 0 0

fedest.com, questions and answers